2022
DOI: 10.4258/hir.2022.28.3.188
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Digital Therapeutics: Present and Future

Abstract: Objectives: Digital therapeutics (DTx) are software-based therapeutic interventions based on clinical evidence. Randomized clinical trials (RCTs) are often the source of clinical evidence, similar to conventional drugs or medical devices. However, novel approaches such as the use of real-world data or digital biomarkers are also utilized. This article aimed to review how DTx products have been clinically evaluated. Methods: DTx products approved by the US Food and Drug Administration as of 2020 were reviewed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…However, these characteristics of DTx can cause a digital health gap due to digital disparities; therefore, a design process considering patient equity is required. Additionally, to secure the therapeutic effect of DTx, patient engagement is key 13,14 , and can be affected by sociocultural background and demographic characteristics 12,13 . The fact that DTx are influenced by demographic or sociocultural characteristics is not sufficiently empirically proven.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these characteristics of DTx can cause a digital health gap due to digital disparities; therefore, a design process considering patient equity is required. Additionally, to secure the therapeutic effect of DTx, patient engagement is key 13,14 , and can be affected by sociocultural background and demographic characteristics 12,13 . The fact that DTx are influenced by demographic or sociocultural characteristics is not sufficiently empirically proven.…”
Section: Discussionmentioning
confidence: 99%
“…Among the clinical trials investigated in this study, no cases of multinational clinical trials were found, and clinical trials in Asia were also rare. In addition, DTx as software can appear in various forms compared with placebos of pharmaceuticals, and maintaining complete blind conditions is difficult 12,49 ; thus, an RCT framework considering the characteristics of DTx should be designed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of Digital Therapeutics (DTx) has been recently established as "evidenced-based therapeutic interventions driven by high-quality software programs to prevent, manage, or treat a medical disorder or disease" by the Digital Therapeutics Alliance. The utilization of DTx in practice involves the presentation of therapeutic solutions for medical or psychological conditions through smartphone applications (apps) or wearable devices 39 .…”
Section: Discussionmentioning
confidence: 99%
“…DTx and related concepts Regulatory bodies have held that DTx need to be clinically evaluated regarding efficacy, safety, and quality. The first aspect of clinical evaluation describes the conscientious, explicit and judicious use of currently accepted best practices to show evidence of the efficacy of a DTx (cf Sackett 1996;Huh et al 2022)…”
mentioning
confidence: 99%